2023
DOI: 10.1088/1361-6528/acae5e
|View full text |Cite
|
Sign up to set email alerts
|

Bias field orientation driven reconfigurable magnonics and magnon−magnon coupling in triangular shaped Ni80Fe20 nanodot arrays

Abstract: Reconfigurable magnonics has attracted intense interest due to their myriad advantages including energy efficiency, easy tunability and miniaturization of on-chip data communication and processing devices. Here, we demonstrate efficient reconfigurability of spin-wave dynamics as well as spin-wave avoided crossing by varying bias magnetic field orientation in triangular shaped Ni80Fe20 nanodot arrays. Particularly, for a range of in-plane angle of bias field, we have achieved mutual coherence between two lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Recognizing these challenges, the field underwent a transition towards nanoscale magnonics, driven by the aspiration for enhanced miniaturization and compatibility with complementary metal-oxidesemiconductor technology. In response to the identified gaps in current research, recent literature has made substantial strides in unveiling the intricate phenomenon of magnon-magnon coupling within irregularly shaped hexagonal dots [50], triangular [61], diamond nanodots [62], cross-shaped nanomagnets [63][64][65], and nanoring arrays [66]. These investigations represent a pivotal advancement towards bridging the existing knowledge deficiencies in the field.…”
Section: Magnon-magnon Coupling In Magnetic Nanostructuresmentioning
confidence: 99%
“…Recognizing these challenges, the field underwent a transition towards nanoscale magnonics, driven by the aspiration for enhanced miniaturization and compatibility with complementary metal-oxidesemiconductor technology. In response to the identified gaps in current research, recent literature has made substantial strides in unveiling the intricate phenomenon of magnon-magnon coupling within irregularly shaped hexagonal dots [50], triangular [61], diamond nanodots [62], cross-shaped nanomagnets [63][64][65], and nanoring arrays [66]. These investigations represent a pivotal advancement towards bridging the existing knowledge deficiencies in the field.…”
Section: Magnon-magnon Coupling In Magnetic Nanostructuresmentioning
confidence: 99%
“…In the last decade, extensive studies have been done using both confined and propagating magnons in the field of magnonics, which emerged as an exciting field of research. To this end single nanomagnets have been studied extensively due to their geometrically confined rich volume and localized magnetic modes [25][26][27][28][29][30][31] in nanometer dimension and their tunability with different external parameters. Therefore, such systems possess great potential in quantum magnonics with the possibility of developing magnon-based on-chip quantum information processing systems in the GHz and THz frequency range with high energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, fundamental research on nanoscale magnonics has demonstrated great promise in developing next-generation high-speed and energy-efficient technology. Novel nanopatterned magnetic structures have emerged as the elevators for upsurging this exciting research field. Magnonics render several prime advantages, e.g., shorter wavelength of spin-wave (SW) or magnon, large scalability, nonreciprocity, waveguiding property, nonlinearity, anisotropic dispersion, reconfigurable band structure, and hybridization with other quasi-particles, leading to the possibility of its myriad applications. These potential applications of magnonics are envisaged with low-loss sustainability, such as SW filter, transistor, , phase shifter, multiplexer, logic gates, directional couplers, memory, SW diodes, and nonreciprocal devices in addition to wave-based computing, , signal processing, and more recently in neuromorphic computing. Such rapid progress toward future technology demands the exploration of fundamental physics in a variety of systems including bi- and multicomponent magnonic crystals, which may provide perfect testbeds for tuning the dipole-exchange coupling of the nanomagnets.…”
Section: Introductionmentioning
confidence: 99%